Evolution of benzodiazepine receptor agonist prescriptions in general practice: A registry-based study - Coteur, Kristien; Mamouris, Pavlos; Vaes, Bert; Van Nuland, Marc; Matheï, Catharina; Schoenmakers, Birgitte (Frontiers in Public Health, 2022)
Background Contrary to most European guidelines, benzodiazepine receptor agonists (BZRA) are often used continuously at a low dosage, being the most common form of long-term use. In Belgium, BZRA use is monitored by analyzing self-report data about medication use in the last 24 h. This method provides insufficient insight into the terms of use of these psychoactive drugs. Aim To describe trends in BZRA prescribing in Flanders, Belgium, between 2000 and 2019. Design and setting Population-based trend analysis and a case-control study for the year 2019 were done with data from a morbidity registry in general practice. Methods Repeated cross-sectional and joinpoint regression analyses revealed trends in sex- and age-standardized prescription rates among adult patients (18+). Results Overall, BZRA prescriptions increased. The highest overall increase was found among male patients 18–44 years old, with an average annual percentage change of 2.5 (95% CI: 0.9, 4.3). Among 65+ female patients, a decrease was found since 2006, with an annual percentage change of −0.7 (95% CI: −1.3, −0.1). In 2019, 12% of registered patients received minimally one prescription, long-term use was observed in 5%, back pain was the most common morbidity significantly associated with a rise in BZRA prescriptions, and zolpidem was the most prescribed BZRA (22%). Conclusion Despite some statistically significant decreasing trends, an overall increase in BZRA prescriptions was observed throughout the 19-year study period, especially among long-term users of 18–44 years and 65-plus. Zolpidem became the most prescribed BZRA and warrants more attention.